A light set on a hill : a chronicle of the Cathedral Parish of St. Lucia's, Kotahena, 1760-1987 - Fernando, Placidus M. ([Colombo : J.S.N. Anandarajah, 1988)
Includes a history of St. Lucia's Cathedral, Kotahena.
Keywords: St. Lucia's Cathedral (Kotahena, Sri Lanka) -- History; Kotahena (Sri Lanka) -- Church history